2019
DOI: 10.1177/0300060518818021
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of malignant arrhythmia caused by displacement of the right coronary artery ostium in surgical correction of supravalvular aortic stenosis

Abstract: ObjectiveThis study was performed to identify the effects of different surgical approaches on the right coronary artery ostium in patients with congenital supravalvular aortic stenosis (SVAS) and to determine how to avoid surgically induced right coronary artery occlusion.MethodsThe surgical techniques and outcomes of 91 patients who underwent surgical treatment of SVAS from 2008 to 2015 in our institution were retrospectively reviewed to identify the causes of early death, reoperation, and extracorporeal memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For patients with SVAS, reinterventions were mainly caused by recurrent supravalvular stenosis, distal residual stenosis, aortic insufficiency, and PAS ( 14 16 , 19 , 20 , 30 , 31 , 33 , 35 , 36 , 43 ). The common shape in two-patch repair is an inverted pantaloon-shaped, which widens the aortic root in the non-coronary sinus and the right sinus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with SVAS, reinterventions were mainly caused by recurrent supravalvular stenosis, distal residual stenosis, aortic insufficiency, and PAS ( 14 16 , 19 , 20 , 30 , 31 , 33 , 35 , 36 , 43 ). The common shape in two-patch repair is an inverted pantaloon-shaped, which widens the aortic root in the non-coronary sinus and the right sinus.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing titles and abstracts, 41 citations remained for the full-text screening and 71 records were deleted due to irrelevance to our study. Finally, 27 studies (7, 8,11,14,[16][17][18][19][20][21][22][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were included.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood supply of the RCA decreased after all three operations. Peng and colleagues [30] emphasized that the shape of the patch should be carefully clipped to avoid postoperative myocardium ischemia due to distortion of the RCA after McGoon and Doty repair. We found that the degree of decrease in RCA blood flow after McGoon and Doty repair was greater than that after Brom repair.…”
Section: Discussionmentioning
confidence: 99%
“…As the coronary artery ostia are located at the proximal end of the stenosis, this pressure gradient leads to insufficient blood supply to the coronary arteries, which may cause angina pectoris during childhood. 227 The primary diagnostic method for supravalvular aortic stenosis is echocardiography, which can be used to evaluate the location, form, and severity; mean and maximum gradients; and structure and function of the left ventricle. CMRI and CTA are equally suited for investigating the aorta.…”
Section: Supravalvular Aortic Stenosismentioning
confidence: 99%